Radicalization and Terrorism: Research within the Australian Context - Rahimullah, Riyad Hosain; Larmar, Stephen; Abdalla, Mohamad (International Journal of Criminology and Sociology, 2013)
<!– [if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–> <!– [if gte mso 9]> <![endif]–><!– [if gte mso 10]> <![endif]–> Terrorism perpetrated by some Muslims has become a global phenomenon that has significantly impacted many nations. In the post-September 11 era, Australia has experienced threat of terrorist attacks from organisations including Al-Qaeda and Jemaah Islamiah. In response to this phenomenon the Australian government has heightened security measures and engaged various strategies to counter-radicalization. While the growing body of global research focussing on radicalization and terrorism may inform such strategies, research within the Australian context would provide a cogent platform for assisting in the response to terrorism at a national level. This paper provides discussion focussing on the paucity in literature on the question of radicalization and terrorism. Furthermore, significant gaps in the literature are highlighted and future research recommendations are suggested that would assist in broadening current understanding of the processes of radicalization and terrorism.